Home Numeracy and Preschool Children’s Mathematical Development: Expanding Home Numeracy Models to Include Parental Attitudes and Emotions - Dowker, Ann (Frontiers in Education, 2021)
Most studies suggest that home numeracy is correlated with preschool children’s current mathematical performance, and also predicts their mathematical performance longitudinally. However, this finding is not universal, and some studies do not suggest a close relationship between home numeracy and preschoolers’ mathematical development. There are several possible reasons for the discrepant findings, including the exact nature of numeracy activities provided, and possible unreliability of parental reports of home numeracy. However, parental attitudes might also lead to differing results: because attitudes might influence actual home numeracy provision or the ways in which it is reported; because parental attitudes and beliefs might be transmitted intergenerationally; and because parental mathematics anxiety may interact with home numeracy activities to create early negative emotional associations about mathematics, as some research suggests to be the case with regard to school-age children. There has been a significant amount of research in the first two of these areas, but very little in the third area with regard to preschoolers. It should be seen as an important area for further research.